THE USE OF PICTURE STORY IN TEACHING READING COMPREHENSION TO THE FIFTH GRADE STUDENTS OF SDN 034 SAMARINDA - Antung Firmandana (Kantor Bahasa Kalimantan Timur, 2017)
This paper dealt with students’ problem in the teaching of reading comprehension in elementary school as there were many factors involved. One of those factors was that most of the students were not interested in reading activity because they often found uninteresting materials. Therefore, the researcher wanted to give an interesting lesson in order to make the students more enthusiastic in the learning process. The researcher used picture story as a teaching aid in teaching reading comprehension. The purpose of this study was to know whether there were significant differences in students’ reading comprehension using and without using picture story. The study focused on fifth grade students of SDN 034 Samarinda. It applied Top-Down Reading Model Theory. The design of this study was an experimental design that examined the differences of two sets of data, the experimental group (students who are taught using picture story) and the control group (students who are taught without using picture story). The result of the study revealed that there were significant differences between teaching reading comprehension with and without using picture story.